Sistema informático de gestión de información para los procesos de producción e inventarios en la florícola ROSADEX CIA. LTDA. - Iguamba Túquerres, Jorge Eduardo (2020)
This technological proposal analyzes the information involved in the production processes, as well as in the inventory development on Rosadex Co Ltd Floriculture. It is in order to implement a computer system that increases the productivity of the company and in turn improves the processing of the information collected in each of the units of the floriculture. Via a desktop, the computer system provides a better experience in the information registry, since at present all these processes are done manually, and as a consequence, losses of information and erroneous data are caused. The above computer system will be designed with the most appropriate tools that are at the forefront of technology such as Visual Studio 2017 as a programming language and SQL Server 2017 as a database. To facilitate its development, a methodology was chosen to allow a quality system to be carried out, therefore XP (Extreme Programming) was used. This method is considered one of the sharpest one existing. This methodology focuses on strengthening interpersonal relationships as a key to the implementation and construction of the computer system. It, at the same time, eases the coding of any computer system and as a result, it accelerates the management of information of the production processes and reduce unnecessary expenses for the company.